2002
DOI: 10.1099/00207713-52-6-1937
|View full text |Cite
|
Sign up to set email alerts
|

Stenotrophomonas rhizophila sp. nov., a novel plant-associated bacterium with antifungal properties.

Abstract: A polyphasic taxonomic study was performed on 16 Stenotrophomonas strains from environmental and clinical sources. A group of three plant-associated isolates were shown to be phenotypically different from the other strains. This group formed a separate physiological cluster (B1) with 42 % heterogeneity to the other isolates. The defining characteristics of the new species were as follows : growth at 4 mC and the absence of growth at 40 mC ; the utilization of xylose as a carbon source ; lower osmolytic toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
100
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 46 publications
6
100
0
1
Order By: Relevance
“…Similar results have been obtained in previous studies such as with Stenotrophomonas rhizophila and S. maltophila isolated from the rhizosphere of canola and potatoes showing antifungal properties, and the latter species showing high variability in its antifungal activity (Berg et al, 1999;Minkwitz and Berg, 2001;Wolf, 2002). It has been suggested that the mechanisms of inhibition of fungal isolates of the genus Stenotrophomonas are species dependent.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar results have been obtained in previous studies such as with Stenotrophomonas rhizophila and S. maltophila isolated from the rhizosphere of canola and potatoes showing antifungal properties, and the latter species showing high variability in its antifungal activity (Berg et al, 1999;Minkwitz and Berg, 2001;Wolf, 2002). It has been suggested that the mechanisms of inhibition of fungal isolates of the genus Stenotrophomonas are species dependent.…”
Section: Discussionsupporting
confidence: 78%
“…Obtaining strains of Sphingobacterium, Psychrobacter, Pseudomonas, Serratia, Staphylococcus and Stenotrophomonas from other plant species using culture media with crab and/or shrimp shells as the only carbon source has been reported (Wolf, 2002;Chang et al, 2003;Ribbeck-Busch et al, 2005;Wang et al, 2006;Chang et al, 2009;Wang et al, 2009;Zachow et al, 2009). Likewise, strains of these genera have been reported as rhizobacteria with in vitro antagonistic activity against phytopathogenic fungi, including F. oxysporum, but not for the strain vanillae.…”
Section: Discussionmentioning
confidence: 99%
“…Different species of bacteria that have been associated to other organisms were also characterized, including Vibrio rotiferianus associated with normal microbiota of rotifers (Gomez-Gil et al, 2003), and Microbacterium oxydans and Nocardiopsis alba associated with normal microbiota of different insects (Pidiyar et al, 2004;Rudolf et al, 2009;Patil et al, 2010). Other bacterial species involved in nosocomial infections were isolated, such as Stenotrophomonas rhizophila (normally associated with plants) (Wolf et al, 2002) and Stenotrophomonas maltophilia (Waters et al, 2007). Brevibacterium linens was isolated exclusively from WPD-affected corals.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown that there is considerable genomic diversity within S. maltophilia and that this species consists of at least nine genomic groups (Hauben et al, 1999;Coenye et al, 2004). In addition, four novel Stenotrophomonas species have been described: Stenotrophomonas africana (Drancourt et al, 1997), Stenotrophomonas nitritireducens (Finkmann et al, 2000), Stenotrophomonas acidaminiphila (Assih et al, 2002) and Stenotrophomonas rhizophila (Wolf et al, 2002). The species S. africana was proposed for a single isolate recovered from cerebrospinal fluid.…”
mentioning
confidence: 99%